2009
DOI: 10.1073/pnas.0906920106
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ADP-ribosyl)ation directs recruitment and activation of an ATP-dependent chromatin remodeler

Abstract: Posttranslational modifications play a key role in recruiting chromatin remodeling and modifying enzymes to specific regions of chromosomes to modulate chromatin structure. Alc1 (amplified in liver cancer 1), a member of the SNF2 ATPase superfamily with a carboxy-terminal macrodomain, is encoded by an oncogene implicated in the pathogenesis of hepatocellular carcinoma. Here we show that Alc1 interacts transiently with chromatin-associated proteins, including histones and the poly(ADP-ribose) polymerase Parp1. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
366
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 326 publications
(381 citation statements)
references
References 43 publications
11
366
0
1
Order By: Relevance
“…3D). Comparing the results of the two CHD1L mutants, the mutation of the CHD1L macro‐domain led to a more prominent reduction in the PARP1/CHD1L interaction, indicating that the macro‐domain of CHD1L is the major PAR binding motif, as described by previous biochemical studies 22, 23. Collectively, these data indicate that PAR affinity for CHD1L is crucial for the interaction between PARP1 and CHD1L, especially at the functional macro‐domain, during early reprogramming.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…3D). Comparing the results of the two CHD1L mutants, the mutation of the CHD1L macro‐domain led to a more prominent reduction in the PARP1/CHD1L interaction, indicating that the macro‐domain of CHD1L is the major PAR binding motif, as described by previous biochemical studies 22, 23. Collectively, these data indicate that PAR affinity for CHD1L is crucial for the interaction between PARP1 and CHD1L, especially at the functional macro‐domain, during early reprogramming.…”
Section: Resultssupporting
confidence: 76%
“…3A, right). It has been shown that the macro‐domain of CHD1L serves an essential role for PAR binding and PARP1‐dependent recruitment of CHD1L to DNA damage sites 22, 23. To determine whether the macro‐domain of CHD1L is involved in the PARP1/CHD1L interaction during cell reprogramming, CHD1L wild‐type (CHD1L‐WT) and two mutant types—a helicase‐domain mutant (CHD1L‐K77R) and macro‐domain mutant (hCHD1L‐D723A)—were ectopically expressed in MEFs with OSKM transfection for 6 days.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PCNA is a ring-shaped clamp around DNA that serves as a loading platform for proteins involved in DNA replication and repair [14]. ALC1 is an SNF2-type chromatin remodeling ATPase, which is activated upon PAR binding to its macro domain at DNA damage sites [15,16]. PARP1, PARG, PCNA and ALC1 are all recruited to laser-induced DNA damage sites albeit with distinct recruitment kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…The first catalytic target is the auto-modification domain of PARP1 itself, followed by PARylation of histones and other proteins at DNA damage sites [19,20]. PARP1 promotes chromatin relaxation at DNA damage sites by PARylating and displacing histone H1 [21,22] and recruiting chromatin remodelers such as ALC1 [15,16,23], SMARCA5 [24] and CHD2 [25]. Chromatin relaxation allows access to DNA repair factors, some of which are recruited through binding PAR.…”
Section: Introductionmentioning
confidence: 99%